The lightning thief [compact disc, unabridged] - Riordan, Rick (Riordan, Rick. Percy Jackson & the Olympians (Listening Library), 2005)
Perseus (Percy) Jackson is the son of Poseidon and a mortal woman. Labeled just another difficult youth, he has been in six schools in as many years. But trouble is brewing between the gods. Soon Percy, aided by a satyr and a daughter of Athena, sets out to find a missing thunderbolt that started all the trouble.